The missions of James, Peter, and Paul : tensions in early Christianity - Chilton, Bruce.; Evans, Craig A. (Novum Testamentum, Supplements, 2005)
The Missions of James, Peter, and Paul investigates the nature, diversity, and relationship of three early and important expressions of Judaic Christianity. It is the conviction of the contributors that the Judaic origins of the Christian movement have not been sufficiently understood in both ecclesiastical and academic circles. Comparison with contemporary Judaism is foundational and leads to the question that guides discussion: How did James relate to such prominent figures as Peter and Paul? Given James' own eminence, those relationships must have been hallmarks of his own stance and status, and they open the prospect that we might delineate James' theological perspective more precisely than otherwise possible by means of this contrast with Peter and Paul. That is the reason for the division of the present volume into two parts. The Missions of James, Peter, and Paul is presented in two parts: James and Peter, and James Paul. Several studies investigate the literary and archaeological evidence that clarifies the world in which James, Peter, and Paul lived, while other studies probe exegetical and theological aspects of the discussion.